Pengembangan Kompetensi Sumber Daya Manusia dalam Rangka Meningkatkan Pelayanan di Rumah Sakit Haji Surabaya - Falih Suaedi (Universitas Darussalam Gontor, 2017)
This study aims to describe the development of human resources competencies and factors that inhibit and support the development of human resource competence in order to improve services at Hajj Hospital Surabaya. This research uses qualitative approach. This research uses direct observation method, in-depth interview, FGD, and documentation analysis as data collection technique. The results concluded that the development of human resources competency in RS Hajj Surabaya basically been planned well enough. This is evident from the priority scale applied in the development of human resource competencies, such as which installations become the focus of human resource competency development and what competencies should be developed in each installation due to different characteristics of each other. However, if examined further, the development of human resources competencies in Hajj Hopital Surabaya can not be said evenly, because it still prioritizes employees who have civil servant status rather than honorary.